PENERAPAN NILAI-NILAI DEMOKRASI DALAM PROSES BELAJAR MENGAJAR MELALUIMATA PELAJARAN PENDIDIKAN KEWARGANEGARAAN (Suatu Penelitian Pada SMA Negeri 1 Mila Pidie) - Halik Halik (Jurnal Sosial Humaniora Sigli, 2020)
This research entitled "Application of Democratic Values in Teaching and Learning Process in SMA Negeri 1 Mila Pidie" formulation of the problem; 1) How is the application of democratic values in the teaching and learning process of Civic Education subjects ?, 2) What are the barriers experienced by teachers in applying democratic values in the learning process ?. Research purposes; 1) to know the application of democratic values in teaching and learning process of Civic Education subjects, and 2) to know the obstacles faced by teachers in applying democratic values. This study used descriptive qualitative method. The population of this study is all teachers of Civic Education. using sampling sampling, data collection Observations and in-depth interviews. The results of this study indicate that the application of democratic values in teaching and learning process subjects of Civic Education has been done well by teachers, although there are obstacles experienced by teachers. The conclusion of the researcher are: 1) Application of democratic values; tolerance, cooperation, and consensus, striving to maintain differences, fostering friendship among students, developing mutual understanding of each other, and teaching openness and dialogue, applying diversity values through lecture models and discussions about cultural riches. 2) Obstacles experienced by teachers of this application is the method of teaching and learning that is used for example; a lecture model that can bore students, material democracy is vast. Suggestion; a) To the teacher in the teaching and learning process always prioritize the values of democracy, so that the learning process can be used as a guide to a more effective and efficient. b) To the students in terms of teaching and learning process for the application of democratic values to be more pro-active to implement in taking a decision, policy, resolve conflict, and the achievement of learning objectives and can improve student learning achievement. Keywords: Implementation, Values, and Democracy.